Yoga and cancer-related fatigue during breast cancer treatment: protocol for a randomized clinical trial - Iamara Rodrigues Acosta; Cristine Lima Alberton; Cristiane Rios Petrarca; Stephanie Santana Pinto (Revista Brasileira de Atividade Física e Saúde)
Cancer-related fatigue is one of the symptoms that most impacts the quality of life of patients undergoing treatment for breast cancer. Yoga has been used as a non pharmacological intervention to alleviate symptoms during breast cancer treatment. However, further studies are needed to elucidate and fill possible gaps regarding the effects of Yoga in this population. This article describes the protocol for a randomized clinical trial that aims to analyze the effects of a Yoga program, compared to a control group, on the physical and psychological outcomes of patients diagnosed with breast cancer, undergoing treatment within the Unified Health System (Sistema Único de Saúde - SUS) in the city of Pelotas, Rio Grande do Sul. Thirty women will be randomized into a Yoga or control group. Participants in the Yoga group will undergo a Yoga program associated with health education, twice a week for eight weeks, with each session lasting 60 minutes. The control group will participate only in health education meetings, once a week, also for eight weeks with sessions of 60 minutes. Assessments of cancer-related fatigue, quality of life, pain, functional capacity, and level of leisure time physical activity will be performed before and after the intervention. Data will be analyzed using Generalized Estimating Equations and Bonferroni post-hoc tests (α = 0.05). The study protocol is registered in the Brazilian Clinical Trials Registry under number RBR- 6vk2vjr.